DEVELOPMENTAL CIGARETTE SMOKE EXPOSURE: LIVER PROTEOME PROFILE ALTERATIONS IN LOW BIRTH WEIGHT PUPS - Canales, Lorena (2012)
Cigarette smoke is composed of over 4000 chemicals many of which are strong oxidizing agents and chemical carcinogens. Chronic cigarette smoke exposure (CSE) induces mild alterations in liver histology indicative of toxicity though the molecular pathways underlying these alterations remain to be explored. Utilizing a mouse model of ‘active’ developmental CSE (gestational day (GD) 1 through postnatal day (PD) 21; cotinine > 50 ng/mL) characterized by low birth weight offspring, the impact of developmental CSE on liver protein abundances was determined. On PD21, liver tissue was collected from pups for 2D SDS-PAGE based proteome analysis with statistical analysis by Partial Least Squares-Discriminant Analysis (PLS-DA). Protein spots of interest were identified by ESI-MS/MS with impacted molecular pathways identified by Ingenuity Pathway Analysis. Developmental CSE decreased the abundance of proteins associated with the small molecule biochemistry (includes glucose metabolism), lipid metabolism, amino acid metabolism, and inflammatory response pathways. Decreased gluconeogenic enzyme activity and lysophosphatidylcholine availability following developmental CSE were found and supports the impact of CSE on these pathways. Proteins with increased abundance belonged to the cell death and drug metabolism networks. Liver antioxidant enzyme abundances [Glutathione-S-Transferase (GST) and Peroxiredoxins] were also altered by CSE, but GST enzymatic activity was unchanged. In summary, cigarette smoke exposure spanning pre- and post-natal development resulted in persistent decreased offspring weights, decreased abundances of liver metabolic proteins, decreased gluconeogenic activity, and altered lipid metabolism. The companion paper details the kidney proteome alterations in the same offspring.